Acute Flaccid Quadriparesis: An Uncommon Presentation of Common Disease - Vishal Chandra Sharma; B. Nandakrishna; Sudha Vidyasagar; Muralidhar Varma (Indian Journal of Medical Specialities)
Acute flaccid quadriparesis is a common presentation to the emergency department with multiple etiologies such as paralytic snakebite, Guillain–Barre Syndrome, and periodic paralysis. Periodic paralysis is a rare entity where the patient presents with weakness, proximal more than distal. The cause for periodic paralysis may vary from hypokalemia to thyrotoxicosis. Thyrotoxicosis commonly presents with weight loss, heat intolerance, tachycardia, and nonspecific symptoms such as fatigue and diarrhea. Neurologic manifestations such as thyroid eye disease and proximal myopathy are commonly seen with Grave's disease. We present a case of 24-year-old male presenting with acute onset weakness of both lower limbs and found to have low potassium. Thyrotoxic periodic paralysis was diagnosed from clinical and investigation findings. Weakness improved with potassium supplementation. Hyperthyroidism was treated with carbimazole and propranolol.